Saccharomyces boulardii Combined With Quadruple Therapy for Helicobacter pylori Eradication Decreased the Duration and Severity of Diarrhea: A Multi-Center Prospective Randomized Controlled Trial - Zhao, Yuchong; Yang, Yilei; Aruna,; Xiao, Jun; Song, Jun; Huang, Tizheng; Li, Shuyu; Kou, Jiguang; Huang, Lu; Ji, Dexiong; Xiong, Si; Peng, Wang; et al. (Frontiers in Medicine, 2021)
Background: Whether probiotics helped the Helicobacter pylori eradication was still highly controversial. The non-bacterial Saccharomyces boulardii has demonstrated its efficacy in the treatment of antibiotic-associated and infectious diarrhea. We aim to evaluate the effects of S.boulardii combined with quadruple therapy for H. pylori eradication and associated side effects. Methods: Three hundred and sixty H. pylori-infected patients were recruited in this multicenter, randomized controlled trial. The patients underwent H. pylori eradication treatment were randomized in a ratio of 1:1 into two separate groups that received standard quadruple therapy (Group A) and quadruple therapy plus S. boulardii sachets (Group B) for 14 days. The everyday medication and side-effects records were collected for compliance and adverse effect analysis. All patients accepted 13C/14C-urea breath tests 4 weeks after the therapy completion. Results: S. boulardii and quadruple therapy combined intervention significantly reduced the incidences of overall side-effects (27.8% vs 38.5%, p= 0.034) and diarrhea (11.2% vs 21.2%, p= 0.012) in Group B compared with quadruple therapy alone in Group A, especially reduced the diarrhea duration (5.0 days vs 7.7 days, p= 0.032) and incidence of severe diarrhea (4.7% vs 10.1%, p= 0.040). Intention-to-treat (ITT) analysis and per-protocol (PP) analysis both indicated no statistical differences of eradication rate between Group A and B (ITT: 82.7% vs 85.8%, p= 0.426; PP: 89.7% vs 94.2%, p= 0.146). The joint use of S. boulardii and quadruple therapy markedly improved the overall pre-eradication alimentary symptoms (HR: 2.507, 95% CI: 1.449 - 4.338) recovery. Conclusion: S. boulardii ameliorated H. pylori eradication-induced antibiotic-associated side effects especially reduced the incidence of severe diarrhea and the duration of diarrhea. However, there was no significant effect of S.boulardii on the rate of H. pylori eradication. Trial registration: The protocol had retrospectively registered at ClinicalTrails.gov, Unique identifier: NCT03688828, date of registration: September 27, 2018; https://clinicaltrials.gov/show/NCT03688828